Histological changes during orthodontic tooth movement due to hyperbaric oxygen therapy - Arya Brahmanta; Sutjipto Sutjipto; Ida Bagus Narmada (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2016)
Background: Mechanical force of orthodontics causes changes in periodontal ligament vascularization and blood flow, resulting in biochemical and cellular changes as well as changes in the contour of the alveolar bone and in the thickness of the periodontal ligaments. Hyperbaric oxygen (HBO) therapy is one of many solutions stimulating the growth of new blood vessels and increasing tissue oxygenation. Thus, HBO plays a role in recovery of periodontal ligament and osteoblasts. Purpose: This study aimed to determine the effects of HBO therapy for seven days on periodontal ligament size and osteoblast number in the tension site during bone remodeling in tooth movement. Method: The study was true experimental laboratories with completely randomized control group post test only design. Twenty-four males guinea pigs were randomly divided into three groups. K0 was the control group without any treatment, K1 was the group given a mechanical orthodontic pressure, and K2 was the group treated with the addition of hyperbaric oxygen therapy. The maxillary incisors were moved distally by elastic separator. After HBO therapy on day 7, all of the groups were sacrificed, and then periodontal ligament size and osteoblast number were analyzed by one-way Anova and LSD statistical tests. Result: The results showed significant differences in the size of the periodontal ligament and the number of osteoblasts in the tension site among the groups (p<0.05). Conclusion: HBO therapy at 2.4 ATA for 7 days is effective in recovery of periodontal ligament and increased osteoblast number during bone remodeling in tension area of orthodontic tooth movement.